Trans-subclavian aortic valve replacement with various bioprosthetic valves: Single-center experience - Hacı Ahmet Kasapkara; Abdullah Nabi Aslan; Hüseyin Ayhan; Serdal Baştuğ; Hakan Süygün; Telat Keleş; Tahir Durmaz; Engin Bozkurt (KARE Publishing, 2016)
Objective: Transcatheter aortic valve replacement (TAVR) has been accepted as an alternative to surgery in high risk or inoperable patients with severe aortic stenosis (AS). Although transfemoral approach is the most often preferred means of access, in patients with severe ilio-femoral arteriopathy, other vascular access sites may be required. The aim of the present study was to report our experience with trans-subclavian approach for TAVR using different valve systems. Methods: Among 273 patients undergoing TAVR between June 2011 and May 2016, 10 patients (mean age: 68.3+-7.6 years; 6 males) with high surgical risk were excluded from transfemoral TAVR because of ilio-femoral arteriopathy. Under general anesthesia, 9 of these patients underwent TAVR via left subclavian artery (SCA) and 1 patient via right SCA. Surgical cut-down and closure techniques were utilized in all patients. Eight balloon-expandable Edwards Sapien XT valves (size: one 23 mm, six 26 mm, and one 29 mm) were used, 1 patient received 26 mm balloon-expandable Sapien 3 valve, and 1 patient had 27 mm self-expandable Lotus valve implanted. Results: Procedural success rate was 90%. Mean aortic gradient decreased to 10.6 mmHg from 47.4 mmHg. Emergent surgery was required in 1 patient due to complication of ventricular valve embolization. Thrombus formation at right SCA was detected in 1 patient and resolved with medical therapy. In-hospital mortality was not observed in any patients. Conclusion: Trans-subclavian approach for TAVR is safe and feasible. Proper patient and valve selection concurrent with utilization of multimodal imaging techniques are crucial for successful and uncomplicated procedure.